Integrating Board Games in Primary Classrooms to Build Dynamic Learning Environments: A Systematic Review - Yuliani, Aulia; Juhana, Agus (Lentera: Jurnal Ilmiah Kependidikan, 2025)
In recent years, the development of educational technology has provided various tools to create more interactive and engaging learning methods. One increasingly popular approach is gamification, which has proven effective in enhancing student engagement and motivation. Learning media such as board games hold significant potential to strengthen active student participation, provide enjoyable learning experiences, and foster the development of their social and cognitive skills. Based on this premise, this study aims to analyze the effectiveness of board games as an educational tool to enhance the engagement of elementary school students. The authors employed a Systematic Literature Review to examine research on the effectiveness of board games as an educational medium for improving student engagement in elementary schools. Data mining was conducted using Publish or Perish with relevant keywords such as "board game," "student engagement," and "elementary school." The research process involved selecting articles based on strict inclusion and exclusion criteria. After collecting initial data, the articles were filtered using the PRISMA framework. The study's findings indicate that students who learn using board games exhibit higher levels of engagement and motivation compared to those taught through conventional methods, primarily due to the more interactive and enjoyable learning environment. Gamification elements such as challenges, scores, and rewards effectively enhance students' social and cognitive skills while deepening their understanding of the subject matter. These findings suggest that integrating board games into the elementary school curriculum can be an effective approach to creating a dynamic learning environment that supports students' holistic development.